2013
DOI: 10.1177/1933719113485293
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and Fibrinolytic Indices During the First Trimester of Pregnancy in Women With Polycystic Ovary Syndrome: A Preliminary Study

Abstract: Objective: To evaluate the levels of coagulation and fibrinolytic markers during the first trimester of pregnancy in women with polycystic ovary syndrome (PCOS) and determine the effects of PCOS and obesity on the levels of these hemostatic markers. Methods: A cross-sectional study was conducted in Beijing, China, on women with PCOS (n ¼ 50), healthy women (n ¼ 50), pregnant women with PCOS (n ¼ 50), and healthy pregnant women (n ¼ 50) at 12 weeks of pregnancy. Coagulation and fibrinolytic parameters were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…PCOS has short-term and long-term complications such as obesity, diabetes, dyslipidemia, infertility, and the risk of cardiovascular disease. Besides these, elevated activation of the blood coagulation system of PCOS has been reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…PCOS has short-term and long-term complications such as obesity, diabetes, dyslipidemia, infertility, and the risk of cardiovascular disease. Besides these, elevated activation of the blood coagulation system of PCOS has been reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Conditions other than pregnancy may also increase the risk of thromboembolic events in the gestational period. Shan et al studied pregnant women with or without PCOS during the first trimester of pregnancy and observed that pregnant women with a previous diagnosis of PCOS had a higher procoagulant state due to a higher concentration of activated clotting factors VIII and activated X 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Koiou et al 40 believe that the highest activity of PAI in PCOS patients is dependent on patient body weight, which is elevated in patients with PCOS and obesity. However, Shan et al 29 and Glueck et al 23 reported that elevated PAI activity occurs regardless of the patientʼs body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS are more likely to develop complications of the metabolic syndrome such as obesity, hypertension, dyslipidemia, and diabetes, which are in turn severe risk factors for cardiovascular disease [7]. PCOS patients have elevated activation of the blood coagulation system [9]. Thrombus formation results from the disturbance between pro-thrombotic and anti-thrombotic factors that controls clotting balance: this disturbance may occur due to an ongoing stimulus to thrombogenesis, a defect of the natural anti-coagulant or fibrinolytic system [10].…”
Section: Introductionmentioning
confidence: 99%